Strengthening Service-Oriented Work Culture Through Excellent Service Training for Government Officials at the Regional Technical Implementation Unit for Plantation Crop Protection Development, East Kalimantan Provincial Plantation Office - Agung Solihin; Achmad Tarmizi (Abdimas Paspama, 2026)
Developing a service-oriented work culture is essential for improving the quality of public services and strengthening organizational performance in government institutions. This community service program aimed to enhance the knowledge, awareness, and competencies of government officials at the Regional Technical Implementation Unit (UPTD) for Plantation Crop Protection Development, East Kalimantan Provincial Plantation Office, in implementing a work culture that supports excellent public service. The program employed a participatory training approach consisting of four stages: preparation, training implementation, evaluation, and follow-up. Training activities were conducted through lectures, interactive discussions, case studies, service simulations, and reflection sessions. The training materials covered organizational work culture, public service values, professional ethics, integrity, effective communication, teamwork, and strategies for implementing service excellence. Program evaluation was conducted using pre-test and post-test assessments, participant observations, and feedback sessions to measure improvements in participants' understanding and engagement. The results indicated increased awareness and understanding of service-oriented organizational culture, strengthened commitment to professionalism and public service ethics, and improved communication and teamwork among participants. The collaborative implementation between the university and the partner institution also supported knowledge transfer and organizational capacity development. This community service program demonstrates that participatory training is an effective strategy for strengthening organizational culture and promoting sustainable improvements in the quality of public services.